The March of Time - Weinert, Friedel. author. aut Link
IX, 284 p.
Keywords: The aim of this interdisciplinary study is to reconstruct the evolution of our changing conceptions of time in the light of scientific discoveries. It will adopt a new perspective and organize the material around three central themes, which run through our history of time reckoning: cosmology and regularity; stasis and flux; symmetry and asymmetry. It is the physical criteria that humans choose – relativistic effects and time-symmetric equations or dynamic-kinematic effects and asymmetric conditions – that establish our views on the nature of time. This book will defend a dynamic rather than a static view of time.